APPLICATION OF SULPHATE ROASTING IN PROCESSES OF COMPLEX EXTRACTION OF VALUABLE REDUCTANTS FROM POLYMETALLICAL CONCENTRATE (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The purpose of this investigation is to apply sulphate roasting in hydrometallurgical processing of a polymetallical concentrate obtained by flotation from sulphide ores in Shaumyan deposit. It is shown that by means of sulphate low temperature roasting of a concentrate with subsequent acid leaching of roasting burnt, it is possible to extract such valuable non-ferrous metals, as copper, zinc and lead.
Keywords: sulphate roasting; Shaumyan deposit; polymetallical concentrate; extraction